Answer:
Step-by-step explanation:
It is stated that a function rule takes an input, and converts it into an output, y, by decreasing twice the input by 4.
Let 'x' be the number
Decreasing twice the number 'x' by 4 = 2x-4
Now,
Given the input x = 5
As the output will decrease twice the input (x=5) by 4
Thus, the output = 2(5)-4 = 10-4 = 6
Therefore,
Answer:
m = 3/40
Step-by-step explanation:
4 = 3/4m - 6
m*4 = m(3/4m -6)
4m = m*3/4m + m*-6
4m = 3/4 - 6m
6m + 4m = 3/4
10m = 3/4
m = (3/4)/10
m = 3/40
check:
4 = 3/(4*3/40) - 6
4 = 3/(12/40) - 6
4 = (3*40)/12 - 6
4 = 120/12 - 6
4 = 10 - 6
2+3t
When t is 1
2+3(1)
2+3
5
When t is 4
2+3(4)
2+12
14